Comparative analysis of juvenile sexual offenders, violent nonsexual offenders, and status offenders - Ford, M. E. (Journal of interpersonal violence, 1995)
Juvenile sexual offenders, violent nonsexual offenders, and status offenders were compared using psychometric instruments to assess intrafamily violence, quality of offender social skills, interpersonal relationships, and self-concept. Self-report and record data were gathered on family history, education, behavior problems, criminal history, history of abuse, exposure to pornography, and early childhood memories. Juvenile child molesters were found to have experienced more parental use of violence and to be victims of physical and sexual abuse more often than the other offender groups. Child molesters expressed greater need for control and inclusion in interpersonal relationships and problems related to self-esteem. The content of early childhood memories and exposure to pornographic material differed among the groups. The groups did not differ in assertiveness, self-concept, or family history variables. Implications of these differences for future research are considered